THE USING OF ADOBE FLASH MEDIA ON THE STUDY INTEREST OF TENTH GRADE STUDENT OF TKBB ON THE SUBJECT BUILDING CONSTRUCTION AT THE SMKN-1 PALANGKA RAYA 2014/2015 - Sakresna Putra Nadea; Revianti Coenraad (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2015)
T Based on the observation done by the researcher during PPL II Semester VII Academic Year 2014/2015 in the tenth grade of TKBB at the SMK Negeri 1 Palangka Raya, it was showed that there were some students were lacked of attentions. This is due to the learning media used was used too often repeatedly which made the students felt bored and lacked of attention on the learning activity. From the above problem, it was needed to find a new learning media to rise the interest, excitement and interesting. By using the Adobe Flash media, it was hoped the study interest of the student will emerge. This research used quantitative method approach with correlation type with variable x (adobe flash media) as the influencing variable and variable y (study interest) as the influenced variable. The sample in this research was a total sample since all of the population (24 students) was involved. Data collecting instrument used a questionnaire which referred to likert scale. After the instruments tested, and stated valid to be used in collecting data, then the data will be tested again to fulfill the analysis conditions. If the data deemed eligible, the variable x and y will be analyzed by using correlation analysis namely Product Moment Pearson. It was proved that the rhitung> rtablewith significance level of 95% (Calculate 0,741 > r table 0.423) which means Ha “there was a relationship between the use of adobe flash media with study interest of Building Construction at the SMK Negeri 1 Palangka Raya” was accepted with “strong” correlation level. This research also produced the increase in study interest as of 25%with average increase of study interest of 4,09on the subject Building Construction after the using of adobe flash media, this is based on the study interest of Building Construction before the using of adobe flashmedia with average marks 46,04 orthere was 46 % of the interested students above the average mark, increased to 50,13 or 71 %of the interested student above the average mark.